Entrepreneurship Education: UnemploymentIses, People’s Well Being and Entrepreneurial Intentions among TVET Graduates in Malaysia - Ali Saibon, Ramdzan; Kamis, Arasinah; Zainol, Zuraidah (International Journal of Psychosocial Rehabilitation, 2019)
Entrepreneurship and education play an important role in improving the well-being of the people by opening new career opportunities for the graduate itself and other people too. Entrepreneurship education equips graduates with entrepreneurial knowledge and skills, which can be their source of interest to become an entrepreneur when facing the possibility of not getting hired in the labor market. In this study, the Theory of Planned Behavior (TPB), models of "Entrepreneurial Event" and Economic-Psychological Model of Determinants of Entrepreneurial Intentions are being utilized. This article aims to discusses the issue of unemployment, people’s wellbeing,entrepreneurial intentions and entrepreneurship education in Malaysia. This article could be used as a reference and is expected to assist various parties, especially the Ministry of Education Malaysia (MOE) and TVET institutions to produce successful young entrepreneurs